Localising the global: the use of a postmodernist aesthetic in the fiction of Alain Mabanckou - Ngulube, Innocent Akilimale (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
This thesis explores the use of a postmodernist aesth etic in Alain Mabanckou's oeuvre, namely Blue White Red, African Psycho, Broken Glass, Memoirs of a Porcupine, Black Bazaar, Tomorrow I'll Be Twenty, The Lights of Pointe-Noire, and Black Moses. In particular, I show how and why this Afrodiasporic author localises strategies associated with Western postmodernist writing in an African postcolonial context. My central argument is that if postmodernism is a critique of modernity in the West, then it must also be a respon se to enforced modernity in the African postcolonial context. In mounting this argument, I conduct a close reading of Mabanckou's novels from within the theoretical frameworks of postmodernism and postcolonialism. I demonstrate that Mabanckou's writing adu mbrates the possibility of a postcolonial postmodernism. Since he is a French-Congolese citizen, his writing evinces aesthetic glocalisation. That is, as a postcolonial writer, he conceives of, and inflects, postmodernism differently from a Western writer, for his experiences of and responses to modernity differ from the latter's. Far from replicating a politics of disillusionment and despair that informs, even characterises, Western postmodernist fiction, Mabanckou invests hi s African postcolonial writing with a politics of decolonis ation which problematises the effects of enforced modernity. Postmodernism, in other words, accords Mabanckou an ambivalent position from which he interrogates both Western modernity and its African version. Significantly, in this regard, Mabanckou's writing presents both an extension of and a departure from the pioneering influence of the first generation of African writers such as Chinua Achebe, Ngugi wa Thiong'o, and Wole Soyinka.
Keywords: Mabanckou, Alain, 1966-; Mabanckou, Alain, 1966- -- Blue, white, red; Mabanckou, Alain, 1966- -- African psycho; Mabanckou, Alain, 1966- -- Broken glass; Mabanckou, Alain, 1966- -- Memoirs of a porcupine; Mabanckou, Alain, 1966- -- The Lights of Pointe-Noire; Mabanckou, Alain, 1966- -- Tomorrow I'll be twenty; Mabanckou, Alain, 1966- Black bazaar; Postcolonialism in literature; African fiction (French) -- History and criticism; Postmodernism (Literature)